Repeated Dose Toxicity Study and Developmental and Reproductive Toxicology Studies of a Respiratory Syncytial Virus Candidate Vaccine in Rabbits and Rats. (March 2021) - Stokes, Alan H.; Franklin, Kelle; Fisher, Daniel E.; Posobiec, Lorraine M.; Binazon, Ornella; Tripathi, Niraj; Ringenberg, Michael Alan; Charlap, Jeffrey; Ziejewski, Mary K.; Vemireddi, Vimala; Khanna Weiss, Payal; Majumdar, Ritankar; et al.
Respiratory syncytial virus (RSV) is a leading cause of acute lower respiratory tract infections, and vaccines are needed to treat young children and older adults. One of GSK's candidate vaccines for RSV contains recombinant RSVPreF3 protein maintained in the prefusion conformation. The differences in immune function of young children and older adults potentially require different vaccine approaches. For young children, anti-RSV immunity can be afforded during the first months of life by vaccinating the pregnant mother during the third trimester with unadjuvanted RSVPreF3, which results in protection of the infant due to the transplacental passage of anti-RSV maternal antibodies. For older adults with a waning immune response, the approach is to adjuvant the RSVPreF3 vaccine with AS01 to elicit a more robust immune response. The local and systemic effects of biweekly intramuscular injections of the RSVPreF3 vaccine (unadjuvanted, adjuvanted with AS01, or coadministered with a diphtheria-tetanus-acellular pertussis vaccine) was tested in a repeated dose toxicity study in rabbits. After three intramuscular doses, the only changes observed were those commonly related to a vaccine-elicited inflammatory reaction. Subsequently, the effects of unadjuvanted RSVPreF3 vaccine on female fertility, embryo-fetal, and postnatal development of offspring were evaluated in rats and rabbits. There were no effects on pregnancy, delivery, lactation, or the pre- and postnatal development of offspring. In conclusion, the RSVPreF3 vaccine was well-tolerated locally and systemically and was not associated with any adverse effects on female reproductive function or on the pre- and postnatal growth and development of offspring.